2020
DOI: 10.1186/s12970-020-0339-y
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of physical training on erythrocyte concentrations of iron, phosphorus and magnesium

Abstract: Background: The present study aimed to determine changes occurring in the erythrocyte concentrations of Iron (Fe), Magnesium (Mg) and Phosphorous (P) of subjects with different levels of physical training living in the same area of Extremadura (Spain). Methods: Thirty sedentary subjects (24.34 ± 3.02 years) without sports practice and a less active lifestyle, formed the control group (CG); 24 non-professional subjects (23.53 ± 1.85 years), who perform between 4 and 6 h/week of moderate sports practice without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
(53 reference statements)
1
25
0
Order By: Relevance
“…The materials and methods are the same as described previously in Maynar-Mariño et al, (2020) [4]. However, they are explained again below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials and methods are the same as described previously in Maynar-Mariño et al, (2020) [4]. However, they are explained again below.…”
Section: Methodsmentioning
confidence: 99%
“…The body concentration of micronutrients is usually determined by measuring the trace elements in plasma; however, the plasma concentration of these elements may fluctuate regardless of nutritional status [3]. Previous studies have observed a decrease in erythrocyte concentrations of other macro minerals, such as magnesium, phosphorus and iron in athletes, compared with a control group [4]. However, very few studies have determined the erythrocyte concentrations of trace elements, and the influence of physical training.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [ 32 , 33 , 34 , 35 ] indicate that the concomitant use of vitamin C (ascorbic acid), vitamin A, vitamin E, vitamin B9 (folic acid), vitamin B12 (cobalamin) and vitamin D3 (cholecalciferol) increases the bioavailability and absorption of Fe in the intestinal tract. These absorption enhancers can be provided by diet or direct supplementation preparations.…”
Section: Bioavailability Of Dietary Ironmentioning
confidence: 99%
“…The connotation of physical training should be the training of human body to improve the ability of walking, running, jumping, and throwing. Physical training has its systematic characteristics, that is, the integrity and comprehensiveness of training [6][7][8]. Physical training should combine the characteristics of sports and human body and cross disciplines through multidisciplinary support, and learn from and integrate the excellent achievements and advanced experience in other fields, so as to optimize the bone, joint, muscle, and sports auxiliary system of human body sports system and the large system of sports training in physical training [9,10].…”
Section: Introductionmentioning
confidence: 99%